Effect of Vasoactive Therapy Used for Brain-Dead Donors on Graft Survival After Kidney Transplantation - (:unkn) unknown (ELSEVIER SCIENCE INC, 2018)
Serum catecholamine levels and peripheral vascular resistance decrease after brain death. Vasoactive drugs are used to control these hemodynamic changes and to improve perfusion of the organs. These drugs might have a role in rejection or loss of the graft organ. We aimed to investigate the effects of vasoactive drugs used in the cadaveric donor care on post-transplant renal graft functions. In this retrospective study, medical records of 135 cadaveric donors (270 kidneys) and recipients of these kidneys were evaluated. Correlation analysis was done to assess the data for factors that may cause rejection and graft loss. Vasoactive drug (noradrenaline 49%, dopamine 60%, adrenaline 3%, dobutamine 11%) consumption ratio was 85.8% in donor care. Increased number of noradrenaline infusion days was associated with decreased rates of graft rejection and graft loss. This correlation was not found for dopamine. Results of the Pearson correlation analysis test showed a relation between noradrenaline use and decrease in graft loss and graft rejection. Noradrenaline but not dopamine used in cadaveric donor care decreased the graft rejection rate and graft loss, presumably by improving hemodynamic stability and organ perfusion, although we found no special reason.
Keywords: DOPAMINE; PRETREATMENT; TRIAL